Cannabidiol Exposure During the Mouse Adolescent Period Is Without Harmful Behavioral Effects on Locomotor Activity, Anxiety, and Spatial Memory - Kaplan, J. S.; Wagner, J. K.; Reid, K.; McGuinness, F.; Arvila, S.; Brooks, M.; Stevenson, H.; Jones, J.; Risch, B.; McGillis, T.; Budinich, R.; Gambell, E.; et al. (Frontiers in Behavioral Neuroscience, 2021)
Cannabidiol (CBD) is a non-intoxicating phytocannabinoid whose purported therapeutic benefits and impression of a high safety profile has promoted its increasing popularity. CBD’s popularity is also increasing among children and adolescents who are being administered CBD, off label, for the treatment of numerous symptoms associated with autism spectrum disorder, attention deficit hyperactivity disorder, anxiety, and depression. The relative recency of its use in the adolescent population has precluded investigation of its impact on the developing brain and the potential consequences that may present in adulthood. Therefore, there’s an urgency to identify whether prolonged adolescent CBD exposure has substantive impacts on the developing brain that impact behavioral and cognitive processes in adulthood. Here, we tested the effect of twice-daily intraperitoneal administrations of CBD (20 mg/kg) in male and female C57BL/6J mice during the adolescent period of 25-45 days on weight gain, and assays for locomotor behavior, anxiety, and spatial memory. Prolonged adolescent CBD exposure had no detrimental effects on locomotor activity in the open field, anxiety behavior on the elevated plus maze, or spatial memory in the Barnes Maze compared to vehicle-treated mice. Interestingly, CBD-treated mice had a faster rate of learning in the Barnes Maze. However, CBD-treated females had reduced weight gain during the exposure period. We conclude that prolonged adolescent CBD exposure in mice does not have substantive negative impacts on a range of behaviors in adulthood, may improve the rate of learning under certain conditions, and impacts weight gain in a sex-specific manner.